Exploring parental preferences for childhood obesity prevention program in China: a discrete choice experiment - Ma, Xinyang; Liu, Taoran; Yu, Jing; Gao, Yangyang; LEUNG, Chun Kai; Liang, Shaolin; Akinwunmi, Babatunde O.; Liu, Xinchang; Huang, Jian; Zhang, Casper J. P.; Ming, Wai-kit (BMC public health, 2025)
Childhood obesity has emerged as one of the most critical public health challenges in China. Despite its urgency, the existing research on parental preference for tackling childhood obesity remains insufficient. This study aimed to determine the factors that parents prioritise most when commissioning hypothetical programs that target childhood obesity prevention in China. A discrete choice experiment (DCE) was conducted to assess parental preferences for a hypothetical childhood obesity prevention programme attributes. Recruitment occurred between 20th October 2022 and 30th December 2022, using snowball sampling facilitated through social media platforms. Eligibility criteria were limited to parents with at least one child aged between 5 and 17 years old. Relevant attributes of the childhood obesity prevention programme were identified through a literature review and expert consultation. The study encompassed six attributes, and the coefficient of these different attributes was analysed using multinomial logit models (MNL) and latent class models (LCM). This study, involving 631 participants, demonstrates that in prioritizing attributes of childhood obesity prevention programs, parents place the greatest importance on additional costs (32.36%). This is followed by daily sleep duration (18.42%) and dietary choices (16.49%). A preference for a 9-hour sleep duration is evident (Odds Ratio [OR]: 1.291; 95% Confidence Interval [CI]: 1.186-1.406; p < 0.05, reference: 7 h), as well as a tendency towards high-protein diets over low-fat ones (OR: 1.114; 95% CI: 1.034-1.200; p < 0.05, reference: low-fat diet). School-based exercise is favoured over fitness centres (OR: 0.837; 95% CI: 0.785-0.893; p < 0.001, reference: school-based). A latent class model (LCM) identifies two distinct groups: one preferring school-based exercise, 8-hour sleep, and minimal additional expenses; the other favouring 9-hour sleep and willingness to invest an additional RMB200 for weight control. Both groups prefer high-protein diets and early eating schedules. Understanding parental preferences and concerns is vital for crafting effective public health policies aligned with UN SDGs and the SDH framework. Key elements include promoting balanced diets, ensuring safe exercise spaces, and fostering parental engagement. Collaboration among policymakers, educators, and parents is essential to mitigate childhood obesity.